2020
DOI: 10.1007/s00384-020-03762-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection does not avoid the risk of diverticulitis recurrence—a systematic review of risk factors

Abstract: Purpose Fifteen percent of patients undergoing elective sigmoidectomy will present a diverticulitis recurrence, which is associated with significant costs and morbidity. We aimed to systematically review the risk factors associated with recurrence after elective sigmoidectomy. Methods PubMed/MEDLINE, Embase, Cochrane, and Web of Science were searched for studies published until May 1, 2020. Original studies were included if (i) they included patients undergoing sigmoidectomy for diverticular disease, (ii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Six factors related to recurrence after bowel resection with diverticulitis were identified: younger age and irritable bowel syndrome (preoperative); anastomotic level and uncomplicated recurrent diverticulitis (operative); absence of active diverticulitis on pathology and persistence of postoperative pain (postoperative). According to the results of this study, elective surgery prevents diverticulitis recurrence or colostomy risk 78 …”
Section: Diverticulitismentioning
confidence: 72%
See 1 more Smart Citation
“…Six factors related to recurrence after bowel resection with diverticulitis were identified: younger age and irritable bowel syndrome (preoperative); anastomotic level and uncomplicated recurrent diverticulitis (operative); absence of active diverticulitis on pathology and persistence of postoperative pain (postoperative). According to the results of this study, elective surgery prevents diverticulitis recurrence or colostomy risk 78 …”
Section: Diverticulitismentioning
confidence: 72%
“…According to the results of this study, elective surgery prevents diverticulitis recurrence or colostomy risk. 78 …”
Section: Diverticulitismentioning
confidence: 99%
“…Except for colectomy to remove diseased colon permanently, current leading managements for diverticular disease including medication and endoscopic/laparoscopic surgery cannot prevent the occurrence/recurrence of diverticulitis, bleeding and/or other complications ( Cirocchi et al, 2015 ; Yamada et al, 2015 ; Kaushik et al, 2016 ; Longchamp et al, 2021 ). Developing more effective minimally invasive approaches leading to less complications and lower diverticulosis recurrence are urgently needed both for patients and the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of six studies including 1062 patients operated on for diverticulitis, the rate of PRD was 5.8%. The authors identified six perioperative variables associated with recurrence: younger age [hazard ratio (HR) = 0.96, 95% CI = 0.93–0.99, p = 0.02], preoperative irritable bowel syndrome (33% vs. 12%, p = 0.02), uncomplicated recurrent diverticulitis as the indication for surgery (73% vs. 50%, p = 0.049), colosigmoid anastomosis (OR = 4, 95% IC = 1.1–15, p = 0.033), absence of active diverticulitis on pathology (40% vs. 27%, p = 0.01) and persistence of postoperative pain (HR = 4.8, 95% CI = 1.8–12.5, p < 0.01) [22]. However, this review presented some bias: it included a heterogeneous group of patients with inclusion of both elective and emergent indications, open and laparoscopic approaches and an absence of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…p < 0.05 was considered as significant (in bold). Risk of recurrence according to the presence of independent predictive factors (more than two episodes of diverticulitis before surgery and age < 50 years) = 4, 95% IC = 1.1-15, p = 0.033), absence of active diverticulitis on pathology (40% vs. 27%, p = 0.01) and persistence of postoperative pain (HR = 4.8, 95% CI = 1.8-12.5, p < 0.01)[22].However, this review presented some bias: it included a heterogeneous group of patients with inclusion of both elective and emergent indications, open and laparoscopic approaches and an absence of multivariate analysis. In another study including 361 patients undergoing laparoscopic PS, PRD was observed in 4.2%.A preoperative diagnosis of irritable bowel syndrome [n = 5/15 (33.3%) with recurrence versus n = 42/344 (12.1%) without recurrence, p = 0.02] and uncomplicated recurrent episodes of diverticulitis before surgery [n = 11/15 (73%) versus n = 171/346 (49%), p = 0.049] were significantly associated with PRD in univariate analysis but not after multivariate analysis[13].Young age as a risk factor for recurrence of diverticulitis after conservative medical treatment has been debated for a long time among surgeons.…”
mentioning
confidence: 99%